Retail Web System Upgrading with Strategic Customer Using Threshold Policy - M. Karuna Sree; K. Subrahmanyam (Universitas Islam Sultan Agung, 2015)
This paper mainly deals with the problems that online retailers are facing by some group of strategic customers by upgrading web system and goods pricing. A monopolist price of a product for which stylized dynamic pricing model is considered at the beginning and the price change is done on the product after considering some set of constraints based on the product availability. Due to some network issues sometimes website may get problems at that time there may be a chance of transaction failure for customer during online purchasing. To predict this probability and doing purchasing opinion depending on the belief of Transaction Success Probability (TSP).Considering this there will be a threshold policy for purchasing by customers here it is going to consider it as first one: Customers buy products only if his valuation for products is above threshold (total reduced profit) otherwise they will not take it into consideration. The threshold rises as TSP degrades, or customers turn out to be risk averse. Here we obtain the best cost of each phase and make out the best strategy for online shopping site customizing by threshold and upgrade the system when present TSP is less than threshold. The online trader turns to increase the price if he disregards strategic customer behavior. The value of disregarding strategic customer deeds is significant. The profit loss cost of disregarding strategic customer deeds grows as customer transaction cost rises.